Raising Hydropsyche instabilis Curtis, 1834 and Hydropsyche bulbifera McLachlan, 1878 (Hydropsychidae, Trichoptera) Larvae in the Laboratory: Larval Morphology and Male Genital Characterization - YİLMAZ, Ergin; KÜÇÜKBASMACI, İbrahim (KSU Journal of Agriculture and Nature, 2023)
Observing of life cycle of aquatic insects can be easier and more reliable information can be collected by raising them in a controlled medium in the laboratory. There is insufficient information about larvae and other life stages in many species of aquatic insects. In order to identify and determine them properly, stages of larvae and pupa should be linked with their adult forms. In this study, the larvae of Hydropsyche instabilis Curtis, 1834 and Hydropsyche bulbifera McLachlan, 1878 (Hydropsychidae, Trichoptera) which were collected from the two rivers were reared in the laboratory. Additionally, it was collected detailed information about the morphological characters of larvae and adult forms. Moreover, it has been observed the process of metamorphosis in larvae and the emergence of adults. The morphological characters of the larvae and the male genital structures of the adults were photographed and explained. During the study, raising success of H. instabilis and H. bulbifera species was determined as 17.85% and 15.65%, respectively.
Keywords: Larva yetiştirme; Trichoptera; Hydropsychidae; Genital karakterizasyonu; Larva morfolojisi; Structural Biology; Larvae raising; Trichoptera; Hydropsychidae; Genital characterization; Larval morphology; Yapısal Biyoloji